Sauerstoff in biologischen Systemen - K.H. Winterhalter (CHIMIA)
The toxicity of oxygen through the generation of superoxide anions is discussed. Superoxide dismutase as a detoxifying principle in aerobic cells and organelles is described. Superoxide generation as a byproduct of methemoglobin autooxidation is characterized and its implication in normal and thalassemic erythrocytes is discussed.